RELATION BETWEEN MOTOR AND SITUATIONAL-MOTOR ABILITIES OF SEVENTH AND EIGHTH GRADE STUDENTS PLAYING VOLLEYBALL - Dževad Džibrić,; Adem Ferhatbegović,; Edin Ganić, (Sport Scientific And Practical Aspects, 2025)
Based on a sample of 112 boys seventh and eight grade of Elementary school, age 13 to 15, we applied system of 21 variables, among them 18 variables were to estimate motor abilities and 3 were to estimate situational-motor abilities in volleyball and all is to determine mutual relations. According to results gained with appliance of canonical correlation analysis we can conclude that relations between observed group of variables – motor ability (as predict group of variables) with criteria group of variables (situational-motor abilities) - will result with statistically significant coefficient of canonical correlation.